Giant Epidermoid Cyst of Posterior Fossa-Our Experience and Literature Review - Giacomo Spinato; Piergiorgio Gaudioso; Maurizio Falcioni; Maria Cristina Da Mosto; Salvatore Cocuzza; Antonino Maniaci; Cristoforo Fabbris; Doriano Politi; Tiziana Volo; Emanuele Ferri; Giovanni Cristalli; Lorenzo Mannelli; et al. (SAGE Publishing, 2021)
Introduction. Intracranial epidermoid cysts are the most frequent congenital intracranial lesion. They rare and benign tumors that can present in different clinical situations depending on location and extension of the disease. Diagnosis is obtained with radiological imaging with RM and non-enhanced TC as elective investigating methods. Elective treatment is surgery, based on total/subtotal excision sparring healthy neurovascular structures, considering the benign nature of this lesion. Case Report. In this study we present the case of a 79-year-old woman affected by recidivist epidermal cyst of the posterior fossa. Clinical presentation was characterized by positional subjective vertigo, intense headache localized in the right part of the head increased by Valsalva maneuver and retroarticular subcutaneous swelling. Radiological investigation found a giant epidemoid cyst of the posterior fossa (8,4 x 4,8 x 5,8 cm), treated with surgery. In the postoperative, the patient was fine and no neurological deficit has been encounterd. REVIEW. In this study, we present a review of the literature regarding giant epidermoid cysts of posterior fossa. Only 11 cases were reported before ours, which actually is one of the largest ever described.